The Effect of Using Papaya (Carica papaya L) Leaves on Blood Glucose and Growth Rate of Asian Seabass (Lates calcarifer) - Dasy , Ainayah Luthviani Sinun; Jasmanindar, Yudiana; Djonu, Asriati (MultiTech Publisher, 2024)
This research aims to determine the effect of using papaya (Carica papaya L) leaves on blood glucose and growth rate of Lates calcarifer. This research used a completely randomized design (CRD) with 4 treatments and 3 replications. Treatment A with the addition of papaya leaves powder (C. papaya) of 3.25 g/L, B of 3.75 g/L, C of 4,25 g/L and D as a Control or without the addition of papaya leaves. The parameters measured were blood glucose, absolute growth and survival. The best treatment is treatment A (C. papaya 3.25 g/L) which produced fish blood glucose on the 60th day of 90 mg/dL, 100% survival rate, absolute weight growth and length of 6.43 g and 6.20 cm. .